A cyano-bridged coordination nanotube showing field-induced slow magnetic relaxation. Issue 38 (18th September 2017) - Shao, Dong; Shi, Le; Shen, Fu-Xing; Wang, Xin-Yi
Abstract : Field-induced slow magnetic relaxation was observed in a cyano-bridged nanotube constructed from a pentagonal bipyramidal Co II unit and a hexacyanocobaltate(iii ) anion. Abstract : Field-induced slow magnetic relaxation was observed in a cyano-bridged coordination nanotube constructed from a pentagonal bipyramidal Co II building block and a hexacyanocobaltate(iii ) anion, which represents the first example of a coordination nanotube displaying field-induced single-molecule magnet behaviour.